Ethnic and folk dance in the context of Chinese cultural evolution - Vang Yuyang (ХДАК, 2025)
In the modern context of social development with complex globalization processes and powerful technical progress, the cultural traditions of China are of great interest all over the world. This interest is manifested in the interest in traditional ceremonies, rituals, and worldview systems. Therefore, today almost every aspect of Chinese life is the subject of study. This also applies to traditional dance culture. In order to implement choreographic research based on elements of traditional Chinese culture, it is necessary to deepen theoretical knowledge in this area. Therefore, the theoretical part of the master's thesis is aimed at reducing gaps in the creation of modern choreographic works based on Chinese traditions. Authentic dance culture is based on ethnic and folklore dances, as well as classical Chinese dance, which are the main basis of choreography that reflects the traditions of the Chinese people. Using elements of modern dance and folklore, choreographers create artistic works that arouse great interest among the audience, but the question of the basis and main sources of choreographic works has not been finally resolved, since traditional Chinese dance art has many specific features associated with various external and internal factors, such as regional history, ethnographic structure of the province, geographical conditions, migration processes, interaction with other ethnic groups.
qualification work for obtaining master’s degree in specialty 024 Choreography
Keywords: танці народні китайські; хореографічне мистецтво Китаю